FATWA DAN REALITINYA PADA ZAMAN RASULULLAH - Abd Rahman, Noor Naemah (Jurnal Syariah, 2019)
This article discusses the mea.ning of fatwa and its derivatives in the Qur'iin. It also explains how fatwas during the Prophet's time were issued.